Willingness to Pay for Existence Value of Mangrove Ecosystem in Youtefa Bay, Jayapura, Indonesia - HAMUNA, Baigo; RUMAHORBO, Basa T.; KEILUHU, Henderina J.; ALIANTO, ALIANTO (Journal of Environmental Management and Tourism, 2018)
Mangrove area in Youtefa Bay is very important for the local people’s lives in around the Youtefa Bay. Willingness to pay (WTP) of the local’s people toward the mangrove ecosystem is their appreciation for existence value of mangrove ecosystem. This research explored how much the WTP was given by the local people toward the mangrove ecosystem existence in Youtefa Bay. The data collection was conducted in March to April 2018 located in three villages around the Youtefa Bay, namely Tobati (46 respondents), Enggros (82 respondents) and Nafri Villages (100 respondents). WTP value collection technique used contingent valuation method (CVM). Result of this research showed that there were 92.98% (212 respondents) who were willing to contribute or pay and 7.02 % (16 respondents) were not. The obtained WTP value of respondents ranged between IDR 0 to IDR 200,000.00 with mean WTP of respondent was IDR 56,052.63/year meanwhile aggregate WTP was IDR 28,811,052.63/year. Variables which had significant influence toward WTP value were earnings and participation and seminaries/trainings/workshops regarding to mangrove ecosystem. Meanwhile gender, age, education level and occupation variables didn’t make any significant influence toward the given WTP value amount.